Methodology of Euler Rotation Parameter Estimation Using GPS Observation Data - Henri Kuncoro (Indonesian Journal of Geospatial, 2013)
Abstract. Block model assumes that the plate / block is a rigid body and homogeneous so that its movement behavior can be quantified. The movement of this block can be represented by Euler rotation parameters consisting of Euler pole (latitude and longitude of Euler pole) and the rotation rate. Euler pole represent the location of the point is traversed by rotation axis whereas the rotation rate represent the magnitude and direction of the velocity of the block relative to the axis of rotation. This study explain the most effective methodology in the Euler rotation parameter estimation. One example of the application of this methodology is in Henri study's (2013), namely the Sunda block rotation parameter estimation. The methodology is explained about Euler rotation parameter estimation from the velocities data, strain analysis for defining the block deformation zone, statistical tests, and velocities transformation between the difference reference frame if the velocities data in difference frame are also included. This methodology is good enough to estimate the Euler rotation parameter for all existing blocks.Keywords : Euler pole, block rotastion, methodology